The Impact of Silicon Valley Bank Bankruptcy on Startup Funding - Apriliansyah Apriliansyah; Zuliani Dalimunthe (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research explores how the collapse of Silicon Valley Bank (SVB) influenced startup funding trends in the United States. Using panel data comprising 23,061 startup funding rounds sourced from S&P Capital IQ, the study evaluates shifts in investment behavior before and after the collapse through Ordinary Least Squares (OLS), Difference-in-Differences (DiD), and subsample regression methods. The results show varied impacts depending on the funding stage. Early-stage startups saw a notable 9% rise in funding after the SVB incident, whereas later-stage startups experienced an equivalent 9% decline. Syndicated investments were linked to higher funding amounts at all stages, with more pronounced effects in early-stage rounds. In addition, established tech companies secured significantly less funding compared to non-tech firms in the post-collapse period, highlighting a broader reassessment of valuations within the tech industry. Overall, the findings indicate that the SVB failure led to a reallocation of capital rather than a universal funding downturn, with investors shifting toward more cautious, targeted investments particularly favoring smaller, early-stage ventures amid heightened systemic uncertainty.